US household deficit spending: A rendezvous with reality - Robert W. Parenteau (Levy Economics Institute of Bard College, 2006)
Over the past decade, deficit spending by consumers has supported the United States economy. Research Associate Robert Parenteau analyzes the financial balance of American households and finds that the pace of deficit spending is likely to stall and, possibly, reverse course. This reversion will jeopardize US profit and economic growth, as well as the growth of countries dependent on export-led development strategies. His research supports the position of other Levy Institute scholars who have urged policymakers to recognize the consequences of current imbalances in the US economy.
Keywords: 330; Haushaltsdefizit; Öffentliche Schulden; Private Verschuldung; Sparen; USA